Sharia-Based Financing Eligibility Assessment for Muslim Business Actors in the Micro and Small Enterprises (MSEs) - Abul Mawahib; Alim Syariati; Mustakim Muchlis (Maliki Islamic Economics Journal, 2025)
This study examines the relationship between Islamic personality, Sharia financial literacy, and the moderating role of Islamic appraisal on financing eligibility assessment in the Micro and Small Enterprises (MSEs) sector. Research data was collected by distributing questionnaires to Muslim business owners in Makassar City. The research sample consisted of 220 respondents using a purposive sampling method. The data analysis method employed the Structural Equation Model–Partial Least Squares (SEM-PLS) approach using SmartPLS 4.0 as the data analysis tool. The results indicate that Islamic personality and Sharia financial literacy have a positive and significant effect on financing eligibility assessment. Islamic appraisal has a positive but insignificant effect on financing eligibility assessment. Furthermore, Islamic appraisal has a positive and significant moderating effect on the influence of Islamic personality, but not on the influence of Sharia financial literacy, on the assessment of financing eligibility. This research makes a theoretical contribution to the development of the literature by investigating the influence of Islamic personality aspects, Sharia financial literacy, and Islamic appraisal on Islamic financing assessment for Muslim entrepreneurs in the MSEs. The implication is the need for synergy between entrepreneurs and Islamic financial institutions in building trust in partnership relationships.